Stochastic Range Estimation Algorithms for Electric Vehicles using Data-Driven Learning Models - Scheubner, Stefan (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
This work aims at improving the energy consumption forecast of electric vehicles by enhancing the prediction with a notion of uncertainty. The algorithm itself learns from driver and traffic data in a training set to generate accurate, driver-individual energy consumption forecasts.